Reconstruction of Clothing Menak Sunda Media Planting Values Culture Local Wisdom Sunda - Karmila, Mila; Maeliah, Maly; Suciati, Suciati (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2017)
The scope of this study relates to the reconstruction of the Sunda ethnic clothing, especially in Bandung marvelous fashion with the intention to reinvest the values of local wisdom Sundanese culture. On Sunda marvelous fashion reconstruction used an experimental method with the following stages: a. Making fashion design Menak Sunda, b. Selection of materials/ material, c. Manufacture of clothing Menak Sunda/ Bandung. Experimental method used to reintroduce a form of fashion Menak Bandung to the public. The results showed that clothing menak Sundanese source can be found in museums Prabu GESAN Ulun is Menak Clothing Bandung. Reconstruction fashion Menak also functions as a medium in instilling the values of local wisdom of Sundanese culture, especially related to the fashion area of Indonesia. Clothing is a cultural phenomenon in a culture, because it is through the visual language/ visualization of clothing, it can be studied, explored and revealed the values contained therein. It also can be a communication medium that has a historical past and the meaning of positive values for the local culture then submitted at the present or future. Â